Transforming Vocational Schools: Socialization and Motivation for Effective Bullying Prevention - Vinola, Okky Ria; Mukarromah, Wahdatur Rike Uyunul; Ghofar, Abd.; Fitriany, Aulia (International Journal of Sustainable English Language, Education, and Science, 2025)
Bullying remains a pervasive issue in vocational high schools, adversely affecting students’ psychological well-being, academic performance, and social development. This study aims to implement socialization and training programs to prevent bullying by raising awareness, enhancing peer relationships, and equipping students and educators with effective prevention strategies. Using qualitative methods, the study identifies challenges such as the trivialization of bullying and the influence of social media, and evaluates the effectiveness of school-based interventions. The findings suggest that comprehensive, community-involved approaches are essential to foster safer and more inclusive educational environments